Spatial Variation of the Microbial Community Structure of On-Site Soil Treatment Units in a Temperate Climate, and the Role of Pre-treatment of Domestic Effluent in the Development of the Biomat Community - Criado Monleon, Alejandro Javier; Knappe, Jan; Somlai, Celia; Betancourth, Carolina Ospina; Ali, Muhammad; Curtis, Thomas P.; Gill, Laurence William (Frontiers in Microbiology, 2022)
The growth of microbial mats or “biomats” have been identified as an essential component in the attenuation of pollutants within the soil treatment unit (STU) of conventional on-site wastewater treatment systems (OWTSs). This study aimed to characterize the microbial community which colonizes these niches and to determine the influence of the pre-treatment of raw-domestic wastewater on these communities. This was done through a detailed sampling campaign of two OWTSs. At each site the STU areas were split whereby half received effluent directly from septic tanks, and half received more highly treated effluent from packaged aerobic treatment systems (a coconut husk media filter on one site , and a rotating biodisc contactor (RBC) on te other site). Effluent from the RBC had the higher level of pre-treatment ( 90% Total Organic Carbon (TOC) removal), compared to the media filter ( 60% TOC removal). Ninety-two samples were taken from both STU locations and characterized by 16S rRNA gene sequencing analysis. The fully treated effluent from the RBC resulted in greater microbial community richness and diversity within the STUs compared to the STUs receiving partially treated effluent. The microbial community structure found within the STU receiving fully treated effluent was significantly different from its septic tank, primary effluent counterpart. Moreover, the distance along each STU appears to have a greater impact on community structure than depth in each STU. Our findings highlight spatial variability of diversity, Phylum- and Genus-level taxa, and functional groups within the STUs, which supports the assumption that specialised biomes develop around the application of effluent under different degrees of treatment and distance from the source. This research indicates that the application of pre-treated effluent infers significant changes to microbial community structure, which in turn has important implications for the functionality of the STU and consequently the potential risks to public health and the environment